The Consciousness Development of Local People Towards Local Vegetable Conservation at Mae Sai Sub-district, Phayao Province - Praditsathaporn, Chanita; Mahavanasin, Laor; Suti, Prakaidao (Area Based Development Research Journal, 2019)
The objective of this participatory action research is to develop the consciousness of local people on conservation of local vegetables at Mae Sai sub-district, Muang district, Phayao province. The sample group is purposive sampling from 17 health developers, 25 youth leaders and 30 household representatives from 10 areas in Mae Sai sub-district. The research method is divided into 3 phases: 1) Situation analysis, 2) Development of consciousness among the local people on conservation of local vegetables of which participation process comprising 6 activities: forest ordination activities, cross-age activities between the elderly and children, campaign for local vegetable and local food consumption, young detective activities, campaign on vegetable-eating kids, activities towards edible waste, and 3) Lesson learned. For qualitative data collection, several instruments are employed. First, to assess the community ways of life, seven tools are in use: mapping, history, calendar, interesting people, family tree, health system, and the community organization. Data are collected by in-depth interview techniques and questionnaire, and analyzed through word-by-word transcription with triangular technique and content analysis techniques. The quantitative data are collected by questionnaire to measure the youth’s consciousness levels towards community development, and analyzed with t-test analysis. The study reveals that the health developers feel happy, are proud, and appreciate the value of local wisdom. That is why they brainstorm and organize activities to promote local vegetables conservation for children, youth and people in the community. The findings reflect that the youths, after the activities, have significantly improved the awareness level of value appreciation at 0.001, and the level of perception and response at 0.05. It is also found that 46 percent of parents whose children are under the Children Development Center do not prepare crunchy snacks in their child’s school bags. Instead, they create a menu from vegetables for children at home. Then the community develops regulations in order to grow vegetables at home, to build edible fences, and to sell organic vegetables and to manage the wet waste.